Mechanical-physicochemical properties and biocompatibility of catechin-incorporated adhesive resins - Fonseca, Beatriz Maria [UNESP]; Barcellos, Daphne Camara [UNESP]; Silva, Tânia Mara da [UNESP]; Borges, Alexandre Luis Souto [UNESP]; Cavalcanti, Bruno das Neves; Prakki, Anuradha; Oliveira, Hueder Paulo Moisés de; Gonçalves, Sérgio Eduardo de Paiva [UNESP] (FapUNIFESP (SciELO), 2019)
Several anti-proteolytic dentin therapies are being exhaustively studied in an attempt to reduce dentin bond degradation and improve clinical performance and longevity of adhesive restorations. Objectives: This study assessed the effect of epigallocatechin-3-gallate (EGCG) on long-term bond strength when incorporated into adhesives. Material and Methods: Adhesive systems were formulated with EGCG concentrations of 0 wt%: (no EGCG; control); 0.5 wt% EGCG; 1.0 wt% EGCG, and 1.5 wt% EGCG. Flexural strength (FS), modulus of elasticity (ME), modulus of resilience (MR), compressive strength (CS), degree of conversion (DC), polymerization shrinkage (PS), percentage of water sorption (%WS), percentage of water solubility (%WL) and cytotoxicity properties were tested. Dentin microtensile bond strength (µTBS) was evaluated after 24 h and again after 6 months of water storage. The adhesive interface was analyzed using scanning electron microscopy (SEM). Results: No significant differences were found among the groups in terms of FS, ME, MR, CS and PS. EGCG-doped adhesives increased the DC relative to the control group. EGCG concentrations of 1.0 wt% and 0.5 wt% decreased the WS of adhesives. WL decreased in all cases in which EGCG was added to adhesives, regardless of the concentration. EGCG concentrations of 1.0 wt% and 0.5 wt% reduced cytotoxicity. EGCG concentrations of 1.0 wt% and 0.5 wt% preserved µTBS after 6 months of storage, while 1.5 wt% EGCG significantly decreased µTBS. SEM: the integrity of the hybrid layer was maintained in the 0.5 wt% and 1.0 wt% EGCG groups. Conclusion: EGCG concentrations of 1.0 wt% and 0.5 wt% showed better biological and mechanical performance, preserved bond strength and adhesive interface, and reduced cytotoxicity.
Keywords: Catechin; Collagen; Dental adhesives; Dentin-bonding agents